2017
DOI: 10.1111/jpn.12672
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sweet potato vines on performance parameters and some carcass characteristics of rabbits

Abstract: SummaryConventional feedstuffs in Brazil are expensive, which has led to the search for less conventional cheaper and locally available feedstuffs. Thus, this study was carried out to determine the dietary effect of dry sweet potato vines (SPV) on the performance and some carcass characteristics of rabbits. A total of twenty-seven weaned White New Zealand rabbits (14 male and 13 female) 35 days old with an average initial weight of 755 g were allocated into three treatments. Nine rabbits were assigned to each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…Despite many advantages of ruminant anatomical features and digestive physiology, the use of many agro-industrial by-products that have valuable nutritional value(s) as an alternative feed source is quite limited. Since the use of alternative feed sources may provide for a cost benefit in livestock production industry, it has been prominently attractive to determine their nutritional values for animal species among animal nutrition specialists (Klinger 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Despite many advantages of ruminant anatomical features and digestive physiology, the use of many agro-industrial by-products that have valuable nutritional value(s) as an alternative feed source is quite limited. Since the use of alternative feed sources may provide for a cost benefit in livestock production industry, it has been prominently attractive to determine their nutritional values for animal species among animal nutrition specialists (Klinger 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They checked similar nutritional quality, which indicates that BP does not change carcass mass and yield, nor percentage of meat protein. Also, Klinger et al (2017), evaluating the carcass of rabbits fed with different levels (10% and 15%) of SPV used as alfalfa hay substitute found that the treatments did not alter the weight of the carcass or percentages of fat and protein in meat.…”
Section: Meat and Colormentioning
confidence: 99%
“…Considerada uma cultura de importância social, por possuir alto teor nutritivo e de custo baixo (Vargas et al, 2018), a batata-doce era consumida por populações de menor renda, porém observa-se o consumo crescente por pessoas com maior poder aquisitivo, devido ao conhecimento dos aspectos nutricionais favoráveis, assim como maior diversidade de produtos encontrados a partir da batata-doce (Wadl et al, 2018;Campos;Pilon;Melo, 2021). Apesar das raízes serem a principal parte econômica da planta, nas folhas, podem-se encontrar compostos interessantes como; proteínas, fibras, carboidratos, vitaminas A, C e minerais porém também são encontrados baixos níveis de compostos tóxicos, como ácido fítico, cianeto, taninos e oxalato (Mohanraj;Sivasankar, 2014), na forma de silagem, a parte aérea é um complemento à alimentação animal, não comprometendo o desenvolvimento e a saúde destes (Klinger, et al, 2017;Klinger, et al, 2020;Sun et al, 2022).…”
Section: Introductionunclassified